The prison house of the circuit : politics of control from analog to digital - Packer, Jeremy, 1970-; Nuñez de Villavicencio, Paula, 1994-; Monea, Alexander; Oswald, Kathleen, 1982-; Maddalena, Kate, 1978-; Reeves, Joshua (University of Minnesota Press, 2023)
"Through the conceptual vocabulary of the circuit, The Prison House of the Circuit presents a history of digital media as well as a provocative model for thinking about governance and media. The authors ultimately demonstrate how contemporary media came to be mechanisms that create frictionless circulation to maximize control, efficacy, and state power"--